RETRACTED: Safety Index Evaluation and Calibration of Load and Resistance Factors for Concrete Beams Under the Simultaneous Effects of Bending, Shear and Torsion - Azhari, A.; Mesbahi, M. R. (Engineering, Technology & Applied Science Research, 2017)
This article has been retracted at the request of the Editor-in-Chief due to extended similarites with a previously published paper (in Persian). The previously published paper is: F. Jafari, J. Akbari, A. Jahanpur, "Evaluation of Safety Index and Calibration of Load and Resistance Factors for Reinforced Concrete Beams under Bending, Shear and Torsion Demands", Journal of Structural and Contruction Engineering, Article 5, Vol. 3, No. 4, pp. 49-64, 2017 (in Persian) The authors of this paper failed to provide any reasoning regarding the case.